SAMBA: A Multicolor Digital Melting PCR Platform for Rapid Microbiome Profiling (Small Methods 8/2022). Issue 8 (17th August 2022) - Luo, Yongqiang; Cui, Xu; Cheruba, Elsie; Chua, Yong Kang; Ng, Charmaine; Tan, Rui Zhen; Tan, Ker‐Kan; Cheow, Lih Feng
Abstract : Rapid Microbiome Profiling In article number 2200185, Cheow and co‐workers showed that melt curve analysis of multicolor sloppy molecular beacon enables significant expansion of the multiplexing capability in digital polymerase chain reaction.